Recent advances in ocular graft-versus-host disease - Cheng, Xianjing; Huang, Ruihao; Huang, Shiqin; Fan, Wei; Yuan, Rongdi; Wang, Xiaoqi; Zhang, Xi (Frontiers in Immunology, 2023)
Ocular graft-versus-host-disease (GVHD) remains a significant clinical complication after allogeneic hematopoietic stem cell transplantation. Impaired visual function, pain, and other symptoms severely affect affected individuals' quality of life. However, the diagnosis of and therapy for ocular GVHD involve a multidisciplinary approach and remain challenging for both hematologists and ophthalmologists, as there are no unified international criteria. Through an exploration of the complex pathogenesis of ocular GVHD, this review comprehensively summarizes the pathogenic mechanism, related tear biomarkers, and clinical characteristics of this disease. Novel therapies based on the mechanisms are also discussed to provide insights into the ocular GVHD treatment.